2019
DOI: 10.1007/s10040-019-01957-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrated hydrogeological modelling of hard-rock semi-arid terrain: supporting sustainable agricultural groundwater use in Hout catchment, Limpopo Province, South Africa

Abstract: An integrated hydrogeological modelling approach applicable to hard-rock aquifers in semi-arid data-scarce Africa was developed using remote sensing, rainfall-runoff modelling, and a three-dimensional (3D) dynamic model. The integrated modelling approach was applied to the Hout catchment, Limpopo Province, South Africa, an important agricultural region where groundwater abstraction for irrigation doubled during 1968-1986. Since the 1960s, groundwater levels in irrigated areas have displayed extended periods of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…However, groundwater has been studied using different techniques: geothermal techniques (Nwankwo 2015;Nwankwo and Shehu 2015;Olatunji and Musa 2013;Toyin et al 2016), isotope techniques (Adelana et al 2003;Geyh and Wirth 1980;Fillion et al 2014Fillion et al , 2018Selck et al 2018;Kattan 2018;Alemayehu et al 2019;Besser et al 2019), multivariate statistics (Mondal et al 2010;Azhar et al 2015;Yidana et al 2018), univariate statistics (Marghade et al 2010;Selvakumar et al 2017;Wali et al 2018a, b), modeling (Ebrahim et al 2019;Locatelli et al 2019), and chemical indices (Marghade et al 2010;Panaskar et al 2016;Wagh et al 2016). Results obtained from these studies showed groundwater quality is influenced by both the natural geogenic processes and anthropogenic activities.…”
Section: Introductionmentioning
confidence: 99%
“…However, groundwater has been studied using different techniques: geothermal techniques (Nwankwo 2015;Nwankwo and Shehu 2015;Olatunji and Musa 2013;Toyin et al 2016), isotope techniques (Adelana et al 2003;Geyh and Wirth 1980;Fillion et al 2014Fillion et al , 2018Selck et al 2018;Kattan 2018;Alemayehu et al 2019;Besser et al 2019), multivariate statistics (Mondal et al 2010;Azhar et al 2015;Yidana et al 2018), univariate statistics (Marghade et al 2010;Selvakumar et al 2017;Wali et al 2018a, b), modeling (Ebrahim et al 2019;Locatelli et al 2019), and chemical indices (Marghade et al 2010;Panaskar et al 2016;Wagh et al 2016). Results obtained from these studies showed groundwater quality is influenced by both the natural geogenic processes and anthropogenic activities.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of the hydrological cycle, especially in these arid areas with highly variable and event-based rainfall, contrasts strongly with poor data availability, limiting the number of techniques and methods available to researchers and the accuracy of models and predictions (Ebrahim et al, 2019). Our aim was to gather reliable data and to develop a community of practice in the catchment.…”
Section: Methodology: the Concept Of A Living Laboratory And Monitoring Approachmentioning
confidence: 99%
“…Some farmers interviewed felt there was no problem, while others were increasingly worried about increasingly frequent drought events and depleting water levels. Meanwhile, recent modeling suggests a more cyclical and dynamic nature of the aquifer's recharge, rather than straightforward overabstraction (Ebrahim et al 2019). However, increasing climate variability and more frequent drought events may make recharge dynamics more difficult to discern.…”
Section: Case Study: the Doringlaagte South Africamentioning
confidence: 99%
“…First, considering the science and research dimension, there has historically been high uncertainty regarding the aquifer's physical status, though this is slowly improving because of recent hydrogeological modeling (Ebrahim et al 2019). However, data scarcity remains; long-term groundwater level observations are limited because of a degraded monitoring network, as are some issues of data sharing because of distrust between commercial farmers and the government.…”
Section: Applying the Solutionscape To The Doringlaagtementioning
confidence: 99%
See 1 more Smart Citation